PENGARUH VARIASI WAKTU CURAH HUJAN TERHADAP KARAKTERISTIK RIGID PAVEMENT DENGAN METODE KUAT TEKAN BETON - Pataras, Mirka; Astira, Imron Fikri; Jaya, M. Genta Trisna (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2016)
Roads are road transport infrastructures covering all sections of the road, including auxiliary buildings and equipment intended for traffic, located on the soil surface, above the soil surface, below ground and / or water, and above the water surface, except roads trains, lorries, and cable roads. Public roads are roads dedicated to general traffic. Parts of the Road are parts of the road covering the road space, road space, and road control room. (Regulation of the Minister of Public Works, Number: 20 / PRT / M / 2010). There is a term that states that 3 (three) main enemies of the road are the first water, second water and third also water. From it can be stated that water, one of which rain water causes damage or reduce the durability of a road construction.pengaruh curah hujan terhadap karakteristik Rigid Pavement dan kuat tekan beton. There is a term that states that 3 (three) main enemies of the road are the first water, second water and third water. From it can be stated that water, one of the rain water causes damage or reduce the durability of a road construction.